Integrative Approach to Facilitate Fracture Healing: Topical Chinese Herbal Paste with Oral Strontium Ranelate. (31st December 2017) - Siu, Wing-Sum; Shiu, Hoi-Ting; Ko, Chun-Hay; Shum, Wai-Ting; Yu, Ho-Nam; Lau, Clara Bik-San; Hung, Leung-Kim; Leung, Ping-Chung
Abstract : Strontium ranelate (SrR) is one of the pharmaceutical agents reported to be effective on the promotion of fracture healing. This study aimed to evaluate the integrative effect of the oral SrR with a topical Chinese herbal paste, namely, CDR, on facilitation of bone healing. The in vivo efficacy was evaluated using rats with tibial fracture. They were treated with either CDR topically, or SrR orally, or their combined treatments. The in vivo results illustrated a significant additive effect of CDR on SrR in increasing the yield load of the fractured tibia. The in vitro results showed that neither SrR nor CDR exhibited a cytotoxic effect on UMR106 and bone-marrow stem cell (BMSC), but both of them increased the proliferation of BMSC at low concentrations. The combination of CDR at 200  μ g/mL with SrR at 200 or 400  μ g/ml also showed an additive effect on increasing the ALP activity of BMSC. Both SrR and CDR alone reduced osteoclast formation, and the effective concentration of SrR to inhibit osteoclastogenesis was reduced in the presence of CDR. This integrative approach by combining oral SrR and topical CDR is effective in promoting fracture healing properly due to their additive effects on proosteogenic and antiosteoclastogenic properties.